PERSEPSI SISWA TENTANG KOMPETENSI KEPRIBADIAN GURU BIMBINGAN DAN KONSELING/KONSELOR DI SMP N 5 PARIAMAN - Sisrianti, Sisrianti; Nurfarhanah, Nurfarhanah; Yusri, Yusri (Universitas Negeri Padang, 2013)
Personality competency is one of the competencies that should be possessed by the guidance and counseling teacher/counselor. The reality shows that there is guidance and counseling teacher/counselor who still has not had a good personality. The purpose of this study was to describe students perception about the competence of the teacher personality at SMP N 5 Pariaman. This research is descriptive. The study population was SMP N 5 Pariaman which totaling 380 people. Samples were determined using proportional random sampling techniques, which are 71 students. The results reveal student perceptions of competence and personality of guidance and counseling teacher/counselor is quite good.